Point prevalence of complex wounds in a defined United Kingdom population. Issue 6 (8th January 2015) - Hall, Jill; Buckley, Hannah L.; Lamb, Karen A.; Stubbs, Nikki; Saramago, Pedro; Dumville, Jo C.; Cullum, Nicky A.
Abstract Complex wounds (superficial‐, partial‐, or full‐thickness skin loss wounds healing by secondary intention) are common; however, there is a lack of high‐quality, contemporary epidemiological data. This paper presents point prevalence estimates for complex wounds overall as well as for individual types. A multiservice, cross‐sectional survey was undertaken across a United Kingdom city (Leeds, population 751, 485) during 2 weeks in spring of 2011. The mean age of people with complex wounds was approximately 70 years, standard deviation 19.41. The point prevalence of complex wounds was 1.47 per 1, 000 of the population, 95% confidence interval 1.38 to 1.56. While pressure ulcers and leg ulcers were the most frequent, one in five people in the sample population had a less common wound type. Surveys confined to people with specific types of wound would underestimate the overall impact of complex wounds on the population and health care resources.